Forget me knot ebook - Marks, Mary (A Quilting Mystery., 2014)
"Mary Marks has stitched together a very clever plot with a cast of engaging characters in this funny, fast-paced debut mystery." —Laura Levine, author of the Jaine Austen Mysteries Welcome to San Fernando Valley, California, where Martha Rose and her coterie of quilters are enjoying life on the good side of retirement—until murder pulls a stitch out of their plans . . . Martha and her besties Lucy and Birdie are set to expand their Quilty Tuesdays by inviting newcomer Claire Terry into their group. Though at forty Claire's a tad younger than their average age, her crafty reputation could perk up their patchwork proceedings, especially as they prepare for the fancy quilt show coming to town. But when they arrive at Claire's home and find her dead inside the front door, and her exquisite, prize-winning quilts soon missing, Martha is not one to leave a mystery unraveled. Especially if she wants to stop a killer from establishing a deadly pattern . . . Praise for the Quilting Mysteries "What's knot to love? Mary Marks has crafted another winner stitched together with humor and heart—Martha Rose is one gutsy lady." —Rochelle Staab, national bestselling author of the Mind for Murder Mysteries "Mary Marks had me on pins and needles and wanting to wrap myself up in a warm quilt while reading her cozy debut!" —Lee Hollis, author of the Hayley Powell Food & Cocktails Mysteries "A pleasurable and satisfying addition to any quilting mystery fan's reading list. Recommend to those who cannot get enough of Terri Thayer, Elizabeth Craig, or Earlene Fowler." — Library Journal